MANAJEMEN PEMBELAJARAN BAHASA ARAB DENGAN PENDEKATAN ACTIVE LEARNING DI PONDOK PESANTREN AL-MUNAWAROH JOMBANG - Ali Maksum; Faizin; Muzdalifah; Ahmad Fachruddin Fajrul I; Suhari (Menara Tebuireng, 2021)
This study focuses on four aspects, namely: (1) how the planning of Arabic learning approach to active learning in boarding school al-Munawaroh Jombang?, (2) how the implementation of Arabic learning approach to active learning in boarding school al-Munawaroh Jombang? , (3) how the evaluation of learning Arabic with active learning approach in boarding school al-Munawaroh Jombang ?, (4) what are the supporting factors and obstacles in learning Arabic with active learning approach in boarding school al-Munawaroh Jombang?. To solve the problems and find the answers to all four issues, this study used a descriptive approach, data collection techniques using interview (interview), observations (observation), and documentation. The results showed that the management of Arabic language learning with active learning approach implemented in boarding school Al-Munawaroh slightly at odds with cognitive active learning that is by rote material. In addition the management carried out on the basis of experience with various modifications following the development of education in Indonesia. Finally, Arabic learning approach to active learning is successful, where learning Arabic that have been the hallmarks of boarding school Al-Munawaroh for the students not only the origin of learning, but really become a necessity of learning that is meaningful to them, as well as materials studied could be linked with experience or existing information on the students' cognitive system. Arabic language learning success is inseparable from the role of management study Arabic implemented from planning, implementation, evaluation, as well as supporting factors and obstacles in its implementation. In order to create an effective learning Arabic, Al-Munawaroh boarding should always develop a learning management in accordance with the development of education today